The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.5539/jas.v2n3p75
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Distribution in Three Introgression Lines of Tomato

Abstract: Total ascorbic acid (total-AsA) content and percentage of reduced ascorbic acid (AsA) on total-AsA were investigated and discussed in fruits, leaves, petiole, stem and roots of the Solanum lycopersicum cv M82 and S. pennellii introgression lines IL7-3, IL10-1 and IL12-4. In fruits, total-AsA content showed to be different according to genotype analysed. Higher total-AsA accumulations were observed for IL7-3 and IL12-4 followed by M82 and IL10-1. Total-AsA was generally higher in leaves than in petioles, stems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Tomato fruits represent a relevant source of ascorbic acid in the human diet. Previous studies identified two ILs with QTLs for ascorbic acid [16,[21][22][23]. In this work, we sought to examine possible differences in the ascorbic acid accumulation among these lines in controlled plant tissue culture conditions, in relation to the maturity stage of the fruit used for the explants and the age of the callus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tomato fruits represent a relevant source of ascorbic acid in the human diet. Previous studies identified two ILs with QTLs for ascorbic acid [16,[21][22][23]. In this work, we sought to examine possible differences in the ascorbic acid accumulation among these lines in controlled plant tissue culture conditions, in relation to the maturity stage of the fruit used for the explants and the age of the callus.…”
Section: Discussionmentioning
confidence: 99%
“…The ascorbic acid content was estimated on fruit pericarp and after 15, 30, 45 and 60 days of in vitro culture from ten randomly chosen calli for each experimental thesis. Samples were taken during the first hours of the light period, weighted, frozen in liquid nitrogen and stored at −80 • C. Ascorbic acid was extracted as reported by [23] and it was measured as previously described [13,37]. AsA quantities were determined by subtracting the reduced AsA (rAsA) from the total Asa (tAsA).…”
Section: Ascorbic Acid Extraction and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation